Can a standardized aptitude test predict training success of apprentices? Evidence from a case study in Switzerland - Michael Siegenthaler (ETH Zurich, KOF Swiss Economic Institute, 2011)
From a theoretical perspective, the output gap is probably the most comprehensive and convincing concept to describe the cyclical position of an economy. Unfortunately, for practical purposes, the concept depends on the determination of potential output, which is an inherently unobservable variable. In this paper, we examine whether the real-time estimates of the output gap as published by the OECD can be improved by referring to measures of physical capital capacity utilisation from business tendency surveys. These data relate directly to the stress on the current capacity to produce goods and services and are not revised. Our real-time panel data set comprises 22 countries at an annual frequency with data vintages from 1995 to 2009. We show that the real-time output gaps are informationally inefficient in the sense that survey data available in real time can help produce estimates that are significantly closer to later releases of output gap estimates.
Keywords: D24; E32; E37; 330; Output gap; capacity utilisation; real-time analysis; survey data; Auszubildende; Qualifikation; Messung; Prognoseverfahren; Betriebliche Ausbildung; Erfolgsfaktor; Schweiz